2017
DOI: 10.1111/jocn.13892
|View full text |Cite
|
Sign up to set email alerts
|

Counselling parents on young children's healthy diet: A modified scoping review

Abstract: Due to inconsistent recommendations and omitted focus on anticipatory counselling on child feeding, parents might perceive pressure and uncertainty related to the child's diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…15 Therefore, dietary counseling should likely to be directed toward the dietary habits of the whole family, not only that of the child. 50 Similarly to the current study's findings, a high maternal education has previously been linked with good dietary habits in children, 10,12,13,51,52 possibly since parents with a lower educational level may have less nutritional knowledge, 53,54 thus potentially limiting the recommended food choices they offer to their children.…”
Section: Discussionsupporting
confidence: 67%
“…15 Therefore, dietary counseling should likely to be directed toward the dietary habits of the whole family, not only that of the child. 50 Similarly to the current study's findings, a high maternal education has previously been linked with good dietary habits in children, 10,12,13,51,52 possibly since parents with a lower educational level may have less nutritional knowledge, 53,54 thus potentially limiting the recommended food choices they offer to their children.…”
Section: Discussionsupporting
confidence: 67%
“…Bringing about new insights within a chosen context of practice is typical of the interpretive description approach. In a recent literature review, no previous studies reflecting our study's aim and objective were found (Holmberg Fagerlund et al, 2017). Analysing data, one may draw inspiration from specific interpretive techniques (Thorne, 2016).…”
Section: Designmentioning
confidence: 93%
“…Anticipatory guidance from the CHC on what the individual parents can expect regarding the development and feeding of their child might influence healthier child feeding habits (Daniels, Mallan, Nicholson, Battistutta, & Magarey, 2013;French et al, 2012). Based on this knowledge, the authors of a recent literature review argued that future studies should evaluate how healthcare providers like PHNs perform appropriate and consistent nutrition counselling in preventive healthcare settings (Holmberg Fagerlund, Helseth, Owe, & Glavin, 2017).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Early life and the transition to family foods therefore represent a significant opportunity to establish a foundation of positive eating behaviors, if parents can be supported to nurture positive food parenting practices, such as encouraging children to listen to their body cues around hunger and satiety. However, parents often feel confused and uncertain about “how” to promote eating behaviors to their young children [ 5 , 6 ]. The field of public health nutrition has long focused on increasing parents’ food literacy, as a pathway to improve positive feeding practices in parents and healthy eating patterns in children [ 7 ].…”
Section: Introductionmentioning
confidence: 99%